Reasonable Understanding: Considerations for Informed Consent in Clinical Research in a Semi-Urban South African Setting - Ilett, Chiara Dianta (Stellenbosch : Stellenbosch University, 2026)
Thesis (MPhil)--Stellenbosch University, 2026.